Integrative Methods: Joining Pharmaceuticals And Nutritional Interferences For Better Health Consequences (Journal of Namibian Studies : History Politics Culture, 2022)
Integrative medicine approaches, which combine conventional pharmaceutical interventions with nutritional strategies, are gaining recognition for their potential to improve health outcomes. This article explores the rationale behind integrative approaches, the evidence supporting their efficacy, and practical considerations for implementation. By harnessing the synergies between pharmaceuticals and nutrition, healthcare practitioners can optimize treatment outcomes and promote holistic wellness.